EVALUASI SALURAN DRAINASE AKIBAT SEDIMENTASI DENGAN MENGGUNAKAN PROGRAM HEC-RAS (CASE STUDY ON JALAN DR. SUTOMO) - Khotibul Umam; M.Tsubutus Surur Al Misbah; Decky Rohmanto (Universitas Islam Nahdlatul Ulama Jepara, 2023)
EVALUATION OF DRAINAGE CHANNEL DUE TO SEDIMENTATION USING THE HEC-RAS PROGRAM (CASE STUDY ON ROAD DR. SUTOMO)Flooding is one of the natural events that can be detrimental to humans. The flood that occurs is in the form of an overflow of water and will inundate lowlands or basins. Floods can also occur as a result of rainwater being trapped in a basin that becomes a puddle or as a result of a water storage container that can no longer accommodate the amount of water that enters it. This study aims to determine: (1). To find out the results of the evaluation of drainage canals on Road Dr. Sutomo, Jepara Regency (2). To find out the results of the evaluation of drainage canals on Road Dr. Sutomo, Jepara Regency, in the existing conditions with the HEC-RAS program (3). To provide solutions to overcome flooding on Road Dr. Sutomo, Jepara Regency. The data collection method used is (1). Field survey (2) Collection of primary data and secondary data (3). Checking data completeness (4). Analyze and evaluate data using HEC-RAS Software. The results showed that the drainage capacity on Road Dr. Sutomo has a discharge of 0.52 m3/s, or the equivalent of 52 liters/s. Shows that with this future drainage condition, it cannot accommodate the incoming water discharge. Because the maximum water discharge from the HEC-RAS calculation is 11.86 m3/sec, or 11860 liters/sec.